Conserving potential coral reef refuges at high latitudes. Issue 3 (24th October 2013) - Beger, Maria; Sommer, Brigitte; Harrison, Peter L.; Smith, Stephen D.A.; Pandolfi, John M.; Cowie, Robert
Abstract Aim High‐latitude coral reef communities composed of tropical, subtropical and temperate species are heralded as climate change refuges for vulnerable tropical coral reef species, giving them high, but as yet unrealized, conservation priority. We review the ecology of subtropical reefs in the context of climate change and evaluate management strategies ensuring both their own continuity and their potential to act as refuges for tropical species. Location Global high‐latitude coral reef environments. Methods We review the literature about refuges management, high‐latitude reefs, climate change effects on reef organisms and the conservation of reefs. Results High‐latitude coral reef systems are functionally different from their tropical counterparts, characterized by unique biogeographical overlap of taxa at their range margins, endemic species and strong seasonality in species composition. They are shaped by marginal environmental conditions, which are predicted to undergo greater changes than reefs at lower latitudes, resulting in community re‐assembly through range shifts, altered dispersal patterns, survivorship and habitat loss. The combined impact of these changes, however, is difficult to assess, as some effects may be antagonistic. Climate change conservation options include passive management strategies such as no‐take reserves that aim to minimize local disturbances, and active strategies such as relocating populations to refuge sites. Success of active intervention relies on the long‐term persistence of relocated populations, which is unlikely for high‐latitude populations once source tropical populations at lower latitudes are locally extinct. Main conclusion High‐latitude reefs are poised for rapid modification under climate change. Management should anticipate these changes by setting up no‐take reserves on suitable subtropical reefs now to foster ecosystem resilience through reduced anthropogenic impacts. Given the uncertainty over which species will arrive or depart and lack of knowledge about the history of most subtropical reef development, active management is presently not the best use of management resources.